The effect of tibial plateau angles on patella ligament thickness after tibial plateau levelling osteotomy in dogs - Bester, Elge (University of Pretoria, 2024)
Mini Dissertation (MMedVet (Small Animal Surgery))--University of Pretoria, 2023.